2015
DOI: 10.1073/pnas.1522163112
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 is a novel therapeutic target for liver fibrosis

Abstract: Liver fibrosis is characterized by the persistent deposition of extracellular matrix components by hepatic stellate cell (HSC)-derived myofibroblasts. It is the histological manifestation of progressive, but reversible wound-healing processes. An unabated fibrotic response results in chronic liver disease and cirrhosis, a pathological precursor of hepatocellular carcinoma. We report here that JQ1, a small molecule inhibitor of bromodomain-containing protein 4 (BRD4), a member of bromodomain and extraterminal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
195
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(212 citation statements)
references
References 27 publications
(20 reference statements)
16
195
0
1
Order By: Relevance
“…It also induces the primary cancer-associated PSCs to become quiescent, as shown by increased lipid droplet accumulation, decreased α-SMA expression, and decreased cell cycle progression. Consistent with our findings, BET inhibitors were recently shown to cause hepatic stellate cells to become quiescent with increased lipid droplet accumulation and decreased collagen I production (13). Furthermore, our findings demonstrating that BET inhibitors do not induce primary cancer-associated PSCs to undergo apoptosis or senescence are in agreement with the lack of effect of BET inhibitors to induce apoptosis or senescence in hepatic stellate cells (13).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It also induces the primary cancer-associated PSCs to become quiescent, as shown by increased lipid droplet accumulation, decreased α-SMA expression, and decreased cell cycle progression. Consistent with our findings, BET inhibitors were recently shown to cause hepatic stellate cells to become quiescent with increased lipid droplet accumulation and decreased collagen I production (13). Furthermore, our findings demonstrating that BET inhibitors do not induce primary cancer-associated PSCs to undergo apoptosis or senescence are in agreement with the lack of effect of BET inhibitors to induce apoptosis or senescence in hepatic stellate cells (13).…”
Section: Discussionsupporting
confidence: 92%
“…They also acquire a myofibroblast-like phenotype and express α-smooth muscle actin (α-SMA) (12). Significantly, a recent report showed that inhibitors targeting the bromodomain and extraterminal (BET) family proteins block activation and function of hepatic stellate cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…Low-molecular-weight fibroblast growth factor 2 (FGF2(lmw)) attenuates hepatic fibrosis by epigenetic downregulation of Delta-like1 [261]. The bromodomain-containing protein 4 (BRD4), a member of bromodomain and extraterminal (BET) proteins highly enriched at enhancers of pro-fibrogenic genes, can be pharmacologically inhibited by its inhibitor, JQ1 to suppress HSC activation [262]. The PPARγ promoter methylation detected in plasma cell-free circulating DNA stratifies mild and severe fibrosis in patients with NAFLD and alcoholic liver disease, although it was more correlated with methylation in hepatocytes than in myofibroblasts [263].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…Interestingly, while these findings identify an important action of the VDR to prevent liver fibrosis, they also highlight the role of the VDR in the disease-potentiating activation of stellate cells, in a process that could be considered analogous to that of differentiation. Further studies of this system identify the role of the chromatin regulator BRD4 in this activity, and suggest that direct inhibition of this downstream factor by a small molecular regulator can bypass the positive effects of a vitamin D analogue (168). …”
Section: The Vitamin D Receptor and Genomic Mechanisms Of Actionmentioning
confidence: 99%